New currentvoltage transferring device with different metals - Masaaki Kando; Norasage Pattanadech (My University, 2015)
A new concept of an electrical shunt with different materials (aluminum and copper) has been developed to be used as an alternative current measurement device. The device provides better current measurement characteristics compared with the conventional current measurement devices such as a shunt resistor with an ammeter or the multiple shunts consisting of molybdenum having a low temperature coefficient and a Rogowski coil with an integrated circuit. The currents in several electrical circuits have been measured using the developed current–voltage transferring device (CVTD) as voltages between the aluminum and copper elements. The measured voltages ( V m ) are proportional to measuring currents ( I m ), which is shown as the following the experimental equation V m [mV] = kI m [A], in which k is a coefficient depending on the configuration of the CVTD. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: Ammeter; Magneto-Optical Properties and Applications